Unmet Need for Contraception Among Female Sex Workers Initiating Oral Pre-Exposure Prophylaxis for HIV Prevention During Kenya's National Scale-Up: Results From a Programmatic Surveillance Study - Kamau, Mercy; Musau, Abednego; Were, Daniel; Waruguru, Gladys; Kabue, Mark; Mutegi, Jane; Plotkin, Marya; Reed, Jason (Frontiers in Global Women's Health, 2022)
Background Female sex workers (FSWs) experience a higher risk for both HIV acquisition and unwanted pregnancies compared to women in the general population. Pre-exposure prophylaxis (PrEP) for HIV prevention offers protection against HIV infection but has no contraceptive effect. We examined the determinants of unmet need for contraception among FSWs who initiated PrEP to inform programs and policies to optimize contraceptive services and avert unwanted pregnancy among this high-risk group. Materials and Methods A cross-sectional analysis was conducted on routine, de-identified client data from a large-scale PrEP service delivery project, from February 2017 to December 2019. Data were collected from FSWs during clinic visits using Ministry of Health approved tools. Records for all 17,456 FSWs initiated on PrEP from 79 health facilities in 10 counties across three geographic clusters with high and medium HIV incidence were examined for eligibility for the analysis. Unmet need for non-barrier contraception was defined as not being pregnant, not currently using the non-barrier contraceptive method, and not trying to conceive or intending to have a child in the near future. Univariate and multivariable regression analyses were conducted with selected variables to examine associations. Results In the 79 sites, eligible records from 17,063 FSWs who initiated PrEP were included. Two-thirds were under 30 years, and the majority were not married and had received PrEP at drop-in centers. Overall, the unmet need for non-barrier contraception was 52.6%, higher for those under 20 years of age (60.9%) and those served in public and private health facilities (67.4 and 83.2%, respectively) rather than drop-in centers (50.6%). Women from the Nairobi and Coast cluster regions reported a higher unmet need for contraception compared to those from the Lake region. All these associations were significant (p < 0.05) at the multivariate level. Conclusions The high unmet need for non-barrier contraception among FSWs initiating PrEP highlights the need for integrated delivery of contraception services within PrEP programs. Identifying groups with a high unmet need could lead to higher success in an integrated program. Two recommended approaches include training healthcare providers to deliver clear contraception messaging during PrEP initiation and making a range of contraceptives accessible within PrEP services for high-risk groups. Furthermore, accelerated research on multipurpose prevention technologies is necessary to reduce the burden on individuals using multiple prevention products concurrently.